A novel growth function incorporating the effects of reproductive energy allocation. - Akihiro Manabe; Takashi Yamakawa; Shuhei Ohnishi; Tatsuro Akamine; Yoji Narimatsu; Hiroshige Tanaka; Tetsuichiro Funamoto; Yuji Ueda; Takeo Yamamoto (PLoS ONE)
Ontogenetic growth functions provide basic information in biological and ecological studies. Various growth functions classified into the Pütter model have been used historically, regardless of controversies over their appropriateness. Here, we present a novel growth function for fish and aquatic organisms (generalised q-VBGF) by considering an allocation schedule of allometrically produced surplus energy between somatic growth and reproduction. The generalised q-VBGF can track growth trajectories in different life history strategies from determinate to indeterminate growth by adjusting the value of the 'growth indeterminacy exponent' q. The timing of maturation and attainable body size can be adjusted by the 'maturation timing parameter' τ while maintaining a common growth trajectory before maturation. The generalised q-VBGF is a comprehensive growth function in which exponentials in the traditional monomolecular, von Bertalanffy, Gompertz, logistic, and Richards functions are replaced with q-exponentials defined in the non-extensive Tsallis statistics, and it fits to actual data more adequately than these conventional functions. The relationship between the estimated parameter values τ and rq forms a unique hyperbola, which provides a new insight into the continuum of life history strategies of organisms.